Partisipasi Perempuan Kelompok Bank Sampah Melalui Pengembangan Bisnis Online Di Desa Tulungrejo Kota Batu: Women’s Participation in Waste Bank Groups Through the Development of Online Businesses in Tulungrejo Village, Batu City - Anggraini, Elok; Sukesi, Keppi (Fakultas Pertanian Universitas Brawijaya, 2025)
Tulungrejo Village, Batu City, is facing challenges in waste management due to the closure of the Tlekung landfill and the low level of public awareness regarding the importance of sustainable waste management. Waste Bank groups have produced various products such as compost, ornamental plants, eco-enzyme products, and beverages; however, their marketing remains suboptimal. One effort to address these issues is through empowering women within Waste Bank groups by developing online businesses or digital marketing as a sustainable circular economy solution. This community service program aims to enhance the capacity of women in Waste Bank groups by providing training in digital marketing strategies. Women members of the Waste Bank will receive assistance in utilizing e-commerce platforms and social media to expand market reach and improve the competitiveness of their products. The approach used in this activity is Participatory Rural Appraisal (PRA), which actively involves the community through outreach, training, demonstrations, and evaluation of program effectiveness. Through this assistance, it is expected that Waste Bank groups will be able to independently develop online businesses, improve household economic welfare, and contribute to establishing Tulungrejo Village as a self-reliant village in waste management and digital economy–based development. With this program, waste management in Tulungrejo Village is expected not only to contribute to environmental sustainability but also to provide economic benefits for women’s groups through the optimization of Waste Bank–based online businesses.